Microfluidic emulsification in food processing. (February 2015) - Maan, Abid Aslam; Nazir, Akmal; Khan, Muhammad Kashif Iqbal; Boom, Remko; Schroën, Karin
Highlights: Microfluidics are used to control droplet size, shape & internal structures. Commercial application is currently not possible due to operational problems. For scale-up, spontaneous devices give an advantage over shear based devices. EDGE systems are unique and produce multiple droplets simultaneously. Commercialization can be achieved by using metal EDGE sieves. Abstract: Microfluidic systems, characterized by micro-meter sized channels, are used in a variety of applications. In foods, the most common application is in the preparation of emulsions where they provide accurate control over droplet size, and shape of internal structures. This paper gives an overview of different microfluidic emulsification techniques i.e., shear driven and spontaneous droplet generation, together with their current limitations. Next a comparison is made on the basis of various parameters affecting the process of emulsification. At the end, an outlook is given on scale-up of microfluidic emulsification for preparation of food-related products.